Intelligent Armbågsortos - Intelligent Elbow Orthosis - Silfveroxel, Oliver; Silberberg, David; Bardun, Gustav (My University, 2024)
Abstract Physiotherapy is crucial for patients with pain or reduced function of muscles and joints. While mechatronic solutions exist to aid care, they are costly, complex, and lack portability. The goal of this project was to construct a smart elbow orthosis to enhance physiotherapy, allowing more accessible and personalized care. This project does not make any claims regarding the clinical efficacy or potential use of the system. The project has consisted of developing multiple different systems from the ground up, including an exoskeleton, tactile sensors, data communication system, and control system. Most of these systems were merged successfully and their functions evaluated. The primary issues encountered concern the communication between devices, and the integration of the controlling algorithms, both of which seem solvable. This limits the current use of the system in following pre-determined trajectories. Data from the tactile sensors can still be collected, though at its current stage, cannot be used to adapt the motion of the orthosis. Although the implementation is not complete, the core idea shows promise, meaning mechatronic solutions might be a valuable step in reducing barriers of entry, and improving care in physiotherapy.